Iontophoresis-assisted versus standard corneal crosslinking for progressive keratoconus - Jia, Hong-Zhen; Pang, Xu; Fan, Zheng-Jun; Peng, Xiu-Jun (Annals of Eye Science, 2017)
Background: To compare the safety and efficacy of iontophoresis-assisted epithelial-on corneal crosslinking (I-CXL) using 0.1% riboflavin-distilled water solution with standard epithelium-off corneal crosslinking (S-CXL) for progressive keratoconus. Methods: In a retrospective analysis, progressive keratoconus patients treated with I-CXL (17 eyes of 17 patients) or S-CXL (13 eyes of 13 patients) were included. All patients were followed up at least 12 months. All patients underwent detailed ophthalmologic examinations involving pre- and postoperative visual acuity, topographic parameters and pachymetry. Intra- and postoperative complications were recorded. Results: No statistically significant differences were observed between the two groups at baseline with respect to visual acuity, age and thinnest corneal thickness (TCT). The postoperative decreases of K1 and Kmean in the S-CXL group represented statistically significantly better results than in the I-CXL group (t=2.093 and 2.123, P=0.046 and 0.043, respectively). Alterations of other parameters showed no significant differences between the two groups. There were no failure cases in the two groups. Conclusions: I-CXL using 0.1% riboflavin-distilled water solution provided effective treatment for progressive keratoconus at 12-month follow-up. However, the decreases of K1 and Kmean caused by I-CXL were less than those by S-CXL. Although treatment time, postoperative patient pain and risk of infection in I-CXL are all less than those in S-CXL, I-CXL is unable to completely replace S-CXL for progressive keratoconus temporarily.